Implementation of Stunting Convergency Actions to the Coverage of Nutrition Sensitive Intervention Programs - Syahrir Syahrir; Yeni Kristina Wengku; Idris Idris; Nurul Fuady Fitryani A; Desi Eka Pratiwi (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Efforts to accelerate stunting will be more effective with specific and sensitive nutrition intervention programs provided in a convergent manner. Programs between government agencies to ensure the availability of each specific nutrition intervention service for priority target families and sensitive nutrition interventions for all groups of people, especially the lower middle class. The purpose of this research was to find out the implementation of stunting convergence action with the scope of sensitive nutrition intervention programs. This research method used a quantitative survey that was analytic in nature with a crossectional study, sampling was porposive sampling with a total sample of 102 subjek taken from a total population of 137 in the working area of PKM Lee, Kolonodale and Petumbea, Morowali Regency North. The results of the study showed that the value of implementing stunting convergence 1 was p-value = 0,000 (p-value<0,05). So, it is said that there is a relationship between the implementation of the stunting convergence action and the coverage of sensitive nutrition intervention programs in North Morowali Regency. It is necessary to make efforts to improve the quality of the program which includes improving the quality of planning, implementation and evaluation where action I which is a situation analysis must be carried out before the process of preparing a work plan local government.